Membrane separation study for methane-hydrogen gas mixtures by molecular simulations - Kovács, T.; Papp, S.; Kristóf, T. (Condensed Matter Physics, 2017)
Direct simulation results for stationary gas transport through pure silica zeolite membranes (MFI, LTA and DDR
types) are presented using a hybrid, non-equilibrium molecular dynamics simulation methodology introduced
recently. The intermolecular potential models for the investigated CH₄ and H₂ gases were taken from literature.
For different zeolites, the same atomic (Si and O) interaction parameters were used, and the membranes were
constructed according to their real (MFI, LTA, or DDR) crystal structures. A realistic nature of the applied potential parameters was tested by performing equilibrium adsorption simulations and by comparing the calculated
results with the data of experimental adsorption isotherms. The results of transport simulations carried out at
25°C and 125°C, and at 2.5, 5 or 10 bar clearly show that the permeation selectivities of CH₄ are higher than the
corresponding permeability ratios of pure components, and significantly differ from the equilibrium selectivities
in mixture adsorptions. We experienced a transport selectivity in favor of CH4 in only one case. A large discrepancy between different types of selectivity data can be attributed to dissimilar mobilities of the components in
a membrane, their dependence on the loading of a membrane, and the unlike adsorption preferences of the
gas molecules. Представлено результати прямих симуляцiй для транспорту стацiонарного газу крiзь чистi кремнеземовi
цеолiтовi мембрани (MFI, LTA i DDR типу), використовуючи недавно запропоновану симуляцiйну методологiю гiбридної нерiвноважної молекулярної динамiки. Моделi мiжмолекулярних потенцiалiв для газiв
CH₄ i H₂, що вивчалися, було взято з лiтератури. Для рiзних цеолiтiв використано однаковi параметри
атомної (Si i O) взаємодiї, а мембрани конструювалися вiдповiдно до їхнiх реальних (MFI, LTA чи DDR)
кристалiчних структур. Реалiстичну природу застосованих параметрiв потенцiалiв протестовано шляхом
здiйснення симуляцiй рiвноважної адсорбцiї i порiвняння обчислених результатiв з експериментальними даними для iзотерм адсорбцiї. Результати симуляцiй транспорту, отриманi при 25°C i 125°C i при 2.5,
5 чи 10 бар, чiтко показують, що селективностi проникнення CH₄ є вищими, нiж вiдповiднi коефiцiєнти проникнення чистих компонент, i значно вiдрiзняються вiд рiвноважних селективностей в адсорбцiї
сумiшей. Селективнiсть переносу на користь CH₄ була спостережена тiльки в одному випадку. Велика
розбiжнiсть мiж двома типами даних для селективностi може бути атрибутом неподiбностi в рухливостi
компонент в мембранi, їхньої залежностi вiд завантаження мембрани, а також вiдмiнностей в адсорбцiйних преференцiях молекул газу